Familial mobilities beyond the private car: electric bikes and car sharing in Sydney, Australia. Issue 1 (2nd January 2020) - Dowling, Robyn; Maalsen, Sophia
ABSTRACT: Mobility practices are one of the central labours of family, through which the relations of kin and non-kin are negotiated. In many cities, the private car has been and is central to familial mobility through the transportation of objects and people, as well as enabling the accomplishment of familial social activities. Recent technological disruptions to transport systems and the increased popularity of non-car modes are challenging such tight interleaving of cars and family. In this paper, we investigate this decoupling of family and private-car-based mobility through a focus on two relatively novel modes: car sharing and electric bikes. Drawing on a qualitative engagement with car sharers and e-bike cyclists in Sydney, Australia, we document how these non-car modes become valued and effective forms of travel for families, and in particular how they facilitate three of the key affordances of the private car for families: carrying, cocooning and convenience. We find that car sharing affords families independent and flexible mobility through a recalibration of convenience. Electric bikes, especially cargo bikes, more easily accommodate the familial needs of carrying objects and people, and are understood as time saving. These two cases, we conclude, help specify the cultural conditions in which the decoupling of family and cars can be more successfully pursued.